2022
DOI: 10.1186/s12877-022-03058-8
|View full text |Cite
|
Sign up to set email alerts
|

Talking about chronic pain in family settings: a glimpse of older persons’ everyday realities

Abstract: Background The expression of chronic pain remains a delicate matter for those older persons who suffer from this condition. If many studies highlight the difficulties of putting pain into words, scarce are those that take into account how given social networks can facilitate or prevent its expression. Based on a qualitative study that explores the communication about chronic pain in older persons’ social network, this article reports on this key issue of talking about health in later life withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Social isolation is common for pain patients (Martinez‐Calderon et al, 2022). Compared with most people on social networks, family members become the primary source of interpersonal communication for pain patients (Merminod et al, 2022). Therefore, family support may be more critical in generating and reducing self‐perceived burdens in pain patients than other social supports.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation is common for pain patients (Martinez‐Calderon et al, 2022). Compared with most people on social networks, family members become the primary source of interpersonal communication for pain patients (Merminod et al, 2022). Therefore, family support may be more critical in generating and reducing self‐perceived burdens in pain patients than other social supports.…”
Section: Discussionmentioning
confidence: 99%
“…However, the small amount of research conducted on this topic has illustrated the importance of understanding these complex dynamics. One study found that the ability of older people to communicate about pain within family networks was both a resource (by allowing people to get help or by strengthening interpersonal relations), and a challenge (by threatening their autonomy, social relations or self-esteem) [ 36 ]. Another scoping review of pain communication in families when parents were experiencing pain, found it was dependent on a number of factors including, the skills that members possess which they perform both individually and together [ 37 ].…”
Section: Discussionmentioning
confidence: 99%